Efficiency of anti-B-cell therapy in patients with neuropsychiatric manifestations of systemic lupus erythematosus: a report of clinical cases - G. M. Koilubaeva; E. A. Aseeva; S. K. Solovyev; N. Yu. Nikishina; E. L. Nasonov; А. S. Dzhumagulova; N. P. Tkachenko; Е. R. Karimova; A. A. Moldobaeva; A. Zh. Zhumakadyrova (Научно-практическая ревматология, 2020)
The paper describes two patients with systemic lupus erythematosus (SLE) with severe nervous system damage characterized by diffuse and focal neuropsychiatric manifestations of SLE due to of the central nervous system involvement and damage to the peripheral nervous system as local mononeuritis of the lower extremities in one case and severe peripheral neuropathy manifested by multiple mononeuritis of the lower extremities in the other. Anti-B cell therapy with rituximab is noted to have an effect.